Parasites in histopathology: A tertiary care hospital experience - Dr. Poovizhi Inbasekaran; Dr. Megala Chandrasekar; Dr. Thamilselvi Ramachandran; Dr. Anbu Lenin Kulandaivel (Tropical Journal of Pathology and Microbiology, 2021)
Background: Parasitic infections are a major public health problem worldwide with one quarter of world’s population is suffering from it. Intestinal and extraintestinal parasitic infestation are raising in developing countries. There is raise in immunocompromised state in which tissue parasitic infestation are increasing  which necessitates this type of study.Method: A retrospective descriptive study with data collected from histopathology register from January 2018 to December  2020, all cases diagnosed as parasitic infestation  with age, gender , location and  histopathological evaluation with tissue response  was analysed.Results: Over the period of 3 years 11 parasitic infestation was identified. 3(27.3%) cases of hydatid cyst, 5(45.5%) cases of  Enterobius vermicularis, 2 (18.2%)case of cysticercosis and 1(9%) case of  hard tick was identified. Most common age group affected was <25 years of age(54.5%). Most common parasite found  is enterobius vermicularis in our study.   Conclusion: A careful histopathological examination to identify  parasitic infestations in tissue sections will help to decrease morbidity and mortality by providing specific treatment to the patient.